The social functions of correctional policy: A case study of the Alabama convict lease system 1845–1928 - McCarthy, Bernard J. (American journal of criminal justice, 1985)
Private sector involvement in corrections is a controversial contemporary practice. This paper examines, from a historical perspective, one state’s experiment with leasing state sentenced convicts to private contractors for use on a variety of for profit labor projects. The convict lease system in Alabama was noteworthy for two reasons: first, Alabama relied on the lease system of convict labor longer than any other state, and second, the state operated one of the most profitable lease systems in the United States. Convicts in Alabama were used in agriculture, road and railway construction, manufacturing, in quarries and in the coal mines. It was in the coal mines that the lease system brought the greatest profit and controversy. Leases with the coal companies for convict labor became a major source of revenue for the state treasury while at the same time, prison reformers criticized the practice for its cruel and inhumane treatment of inmates (the death rate at some of the mining camps exceeded 40% of the inmates under custody per year). In addition, this paper examines some of the social consequences associated with the correctional policy of convict leasing.